Lithological Control on Variations in Total Dissolved Solids (TDS) and pH of Auya River Water, Obano Area, Paniai Regency , Central Papua - Boma, Deserius; Mote, Dance (UIR PRESS, 2026)
This study focuses on the study of the influence of lithology and the level of rock weathering on the water quality of the Auya River located in Obano District, Paniai Regency, Central Papua, using Total Dissolved Solids (TDS) and pH as the main indicators. The approach applied is a quantitative descriptive method, which was carried out through field surveys at six observation points, direct measurement of water quality parameters, and statistical analysis including descriptive statistics, Pearson correlation, and linear regression. The results of the study indicate an increasing trend in TDS and pH values from upstream to downstream, which is related to changes in lithology from intrusive igneous rocks to sedimentary rocks, accompanied by an increase in weathering intensity. The correlation test shows a very strong relationship between TDS and pH (r = 0.975), as well as a significant relationship between water quality parameters with lithology and weathering levels. The results of the regression analysis show that lithology contributes to TDS variations by (84.1%), while the level of weathering affects pH variations by (71.4%). These findings confirm that geological factors play a dominant role in controlling the hydrogeochemical characteristics of river water through the process of mineral dissolution and ion release. Furthermore, the presence of sulfide minerals such as pyrite contributes to increased dissolved ions through natural oxidation processes. Furthermore, anthropogenic activities also contribute to variations in water quality. TDS (17–63 mg/L) and pH (6.6–7.9) indicate that the Auya River water quality remains within clean water quality standards. This study emphasizes the importance of geological aspects as a basis for water quality management in areas with high geological complexity.